Summer bulletin boards : for Sunday school - Jensen,Carolyn Passig (San Diego, Rainbow Books, 1993)
Provides instructions and suggestions for assembly of thirteen seasonal bulletin boards for use in Sunday schools.
Keywords: Bulletin boards in Christian education. Christian education -- Audio-visual aids